(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
This research aims to improve social studies learning outcomes using a problem-based learning (PBL) approach In Class IV students at SDN 7 Telaga Biru , Gorontalo Regency . The research method used is Classroom Action Research. The data collection technique used in this study is a description test while observation and documentation are supporting. The subjects of this study were 22 students of class IV at SDN 7 Telaga Biru. The results showed that in the first cycle, there were 14 students who achieved the minimum completeness criteria with a percentage of 63.6%. This result has not reached the performance indicator of 80%, so it is continued in the next cycle. Cycle II student learning outcomes that achieve the minimum completeness criteria are 19 students with a percentage of 86.36% and have achieved predetermined performance indicators. Thus it was concluded that by using the Problem Based Learning (PBL) approach, social studies learning outcomes for fourth grade students at SDN 7 Telaga Biru, Gorontalo Regency, increased.